Comprehensive analysis of age‐related somatic mutation profiles in Chinese young lung adenocarcinoma patients. (1st March 2019) - Yang, Bo; Li, Jie; Li, Fang; Zhou, Hongxia; Shi, Weiwei; Shi, Huaiyin; Sun, Shengjie; Sun, Wending; Wang, Jinliang; Ma, Junxun; Yan, Xiang; Hu, Yi; et al.
Abstract: Background: Lung adenocarcinoma in young adults is a rare entity with the oncogenic genetic alterations associated being poorly understood. In the present study, the effect of genetic alterations in lung adenocarcinoma patients diagnosed in young patients is reported. Methods: Twenty young lung adenocarcinoma patients (age years: median: 33.5, range: 24‐36) were enrolled in the current study and 24 patients who were at common age of the disease onset (age years: median: 61.5, range: 52‐79) were selected for comparison. Paraffin sections of lung adenocarcinoma were analyzed using the whole‐exome sequencing platform. Results: Similar number of somatic mutations per tumor were found in the young patients and their older counterparts. Although no age‐related differences were detected in the numbers of lung adenocarcinoma patients harboring well‐known gene variants, mutations in FRG1 and KMT2C were associated with a younger age especially after correcting for tobacco smoking and sex ( FRG1 : P = 0.027, KMT2C : P = 0.046). Five genetic variants showed higher alteration frequencies in young patients compared to the unclassified East Asian population, suggesting these mutations as disease‐related hereditary germline variants. Conclusions: These results suggest different characteristics of lung adenocarcinoma between the young and the patients at common age of onset. Young patients with lung adenocarcinoma have a distinctly unique prevalence of oncogenic genetic alterations. Abstract : We found different genomic characteristics of lung adenocarcinoma between the young and the patients at common age of onset, and some changes have clinical information value.